The Impact of High Canopy Vegetation-Atmosphere Storage on Surface Energy Closure over the Eastern Slope of the Qinghai-Xizang Plateau - Yuchen LIU; Maoshan LI; Na CHANG; Yonghao JIANG; Ting WANG; Pei XU (Gaoyuan qixiang)
The phenomenon of near-surface energy budget imbalance is widespread， especially in the complex underlying surface such as mountain lakes.Due to the heterogeneity of the surface， the energy closure is poor， and the influence of the energy storage term between the atmosphere of the high canopy vegetation in the mountain on the energy closure is often ignored.This paper is based on the gradient tower meteorological data， radiation observation data and turbulence observation data of the eddy covariance system of Mount Emei Atmosphere and Environment Comprehensive Observation Experimental Station of Chengdu University of Information Technology （hereinafter referred to as "Mount Emei Station"） from June 2022 to October 2022.The Ogive function was used to analyze the average time suitable for the turbulent flux calculation at the forest station， and the soil heat flux and energy storage between vegetation and atmosphere were calculated， and the changes of near-surface energy balance after considering the storage terms between vegetation and atmosphere were analyzed.The results show that extending the average time to calculate turbulent flux to 60 minutes can capture larger turbulent vortices at some moments to a certain extent， but the energy balance ratio is lower than the average time of 30 minutes， so it is considered that the average time of 30 minutes is still suitable for the calculation of turbulent flux at Emei Mountain Station.The energy storage item of vegetation atmosphere improves the energy balance ratio by about 3.65%.Considering that this item has the effect of improving energy closure in most of the time， the energy storage item of photosynthesis contributes the most to improving energy closure， followed by the heat storage item of vegetation canopy， followed by the sensible heat storage item， and the latent heat storage item contributes the least.All the energy storage items in the atmosphere of high canopy vegetation have obvious single-peak diurnal variation characteristics.The peak value of heat storage items in vegetation canopy can reach up to 26 W·m-2， and the energy balance ratio can be increased by 1.57% when the heat storage items in vegetation canopy are considered.The peak value of the photosynthetic storage term can reach about 8 W·m-2， and the average daily storage capacity is about 141.6 W·m-2， which is the main energy storage term.Considering the photosynthetic storage term， the energy balance ratio can be improved by 1.65%， accounting for 45% of the overall effect.The peak value of sensible heat storage term is about 5 W·m-2， the magnitude of latent heat storage term is very small， and the effect on energy closure is also small.Vegetation-atmosphere storage terms cannot be ignored except latent heat storage terms which are very small.When considering the energy storage between vegetation and atmosphere， the energy closure problem still exists.Therefore， in addition to the energy storage term， the influence of large-scale vortices induced by the underlying mountain surface on the near-surface energy budget also needs to be further studied.